2006
DOI: 10.1677/joe.1.06574
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil-induced hypothyroidism protects ionizing radiation-induced multiple organ damage in rats

Abstract: The objective of this study was to examine the potential radioprotective properties of propylthiouracil (PTU)-induced hypothyroidism against oxidative organ damage induced by irradiation. Sprague-Dawley rats were pretreated with saline or PTU (10 mg/kg i.p.) for 15 days, and were then exposed to whole-body irradiation (800 cGy). A group of rats were decapitated at 6 h after exposure to irradiation, while another group was followed for 72 h after irradiation, during which saline or PTU injections were repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…In the present study, PTU exposed rats showed hypothyroidism which was evidenced biochemically by significant (P<0.05) decrease in serum T3 and T4 levels with significant (P<0.05) increase in serum TSH level as compared to control rats. These results are in agreement with Sener et al (2006) [27] who reported that PTU dramatically reduced thyroid hormones. Serum concentrations of thyroid hormones (T3, T4) and TSH are commonly used as reliable indicators of the thyroid function in humans and experimental animals [42].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, PTU exposed rats showed hypothyroidism which was evidenced biochemically by significant (P<0.05) decrease in serum T3 and T4 levels with significant (P<0.05) increase in serum TSH level as compared to control rats. These results are in agreement with Sener et al (2006) [27] who reported that PTU dramatically reduced thyroid hormones. Serum concentrations of thyroid hormones (T3, T4) and TSH are commonly used as reliable indicators of the thyroid function in humans and experimental animals [42].…”
Section: Resultssupporting
confidence: 93%
“…B.W./day (1 ml/250 g) by i.p. injection for 15 day according to Sener et al (2006) [27]. Blood was collected and the serum was separated to measure T3, T4 and TSH.…”
Section: Induction Of Hypothyroidismmentioning
confidence: 99%
“…The mechanism for this response is an increase in TSH levels due to a decrease in the production of thyroid hormone FT4, FT3 (Sener, et al, 2006). This was evidenced biochemically by reduction in serum thyroid hormone levels of FT4, FT3, TT3 and TT4 with increase in serum TSH level compared to the normal control rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this reduction of neutrophil accumulation may have an anti-oxidant effect or may decrease the generation of lipid peroxidation is not observed in the present study, because at the 24-h of irradiation neither lung nor cardiac tissue demonstrated any irradiation-induced lipid peroxidation. Since IR-induced injury becomes evident at the 72 nd h of irradiation (37), it is expected that this neutrophil-limiting effect of Mg could have a therapeutic value in the long term.…”
Section: Discussionmentioning
confidence: 99%